Dihydroartemesinin and Curcumin Based Self-Microemulsifying Drug Delivery System for Antimalarial Activity - Srivastava, Richa; Fatima, Zeeshan; Sahoo, Jagannath; Joshi, Prince; Tripathi, Renu (Drug Research, 2022)
Malaria is a significant global problem which still persists despite the development of various effective antimalarial drugs. It is challenging to treat this disease due to the parasite’s complex life cycle and high recrudensce of antimalarial drugs. A new self-micro emulsifying drug delivery system has been developed to improve the solubility of dihydroartemisinin and curcumin. The prepared formulation contained Dihydroartemesinin, curcumin, Groundnut Oil, Cremephor RH, and Tween 80. Self-micro emulsification time, zeta potential, droplet size, polydispersity index, transmission electron microscopy, drug release, and in-vivo studies were performed for characterization. The globule size was found to be 25.59±0.40 nm and the zeta potential was-5.75±0.18 mV. The globules prepared were spherical in shape. The in-vitro dissolution performance of formulation of dihydroartemisinin and curcumin self emulsifying drug delivery system showed significantly (p<0.05, Origin Pro 8.5) higher release as compared to the pure drugs. The results of the study suggested that the prepared self emulsifying drug delivery system combination of Dihydroartemesinin and curcumin has a better potential to cure parasitemia as compared to the individual drug.
Keywords: dihydroartemesinin; curcumin; anti-malarial; parasitemia